Fast hybrid-MixNet for security and privacy using NTRU algorithm - Ahmad, Khaleel; Kamal, Afsar; Bin Ahmad, Khairol Amali; Khari, Manju; González-Crespo, Rubén (Journal of information security and applications, 2022)
Security and privacy-enhancing techniques are developed in order to provide strong protection over the Internet. These techniques aim to enable the users to keep their identities secret during the communication when they are forwarding an email, making payments online, and web browsing or posting to newsgroups. MixNet is the most practical solution for concealing the identities of messages and senders. The anonymous channel contains numerous routing protocols that consist of anonymous messages forwarding between nodes. The structure of MixNet is also based on this way to achieve anonymity. After the proposed work of Chaumian MixNet, many practical implementations of MixNet using many approaches and techniques are accomplished until now. In this paper, we propose the hybrid MixNet using NTRU asymmetric cryptosystem. We designed a mechanism for anonymous communication in which more people can participate in their secure communication. It hides the relation between input and output in each phase of Mix servers. The performance of Hybrid MixNet using NTRU is better than Hybrid Mixnet using ElGamal and ECC. In our proposed system, Hybrid MixNet using NTRU takes average time 16.4 milliseconds while Hybrid MixNet using ElGamal and ECC take 93.4 milliseconds and 182.2 milliseconds respectively.
Keywords: mix servers; hybrid MixNet; re-encryption MixNet; decryption MixNet; NTRU algorithm; JCR; Scopus